Math is Easy 5.0 - Othman, Norlida; Mohamed, Nadiah; Yaacob, Nurul Aityqah; Mohd Ruslan, Siti Zaharah; Andu, Yusrina; Ismail, Norul Fadhilah (Universiti Teknologi MARA, Negeri Sembilan, 2025)
The Math is Easy 5.0 program was held on 27 June 2025 for Pre-Diploma and Diploma students taking mathematics courses at UiTM Cawangan Negeri Sembilan, Kampus Kuala Pilah. The program aimed to enhance students’ preparation for final examinations through guided practice using past year exam questions related to their course codes. It helped strengthen their understanding of key mathematical concepts while providing effective problem-solving strategies and exam techniques to improve academic performance.